2016
DOI: 10.1039/c5fo01194a
|View full text |Cite
|
Sign up to set email alerts
|

Dietary arginine and N-carbamylglutamate supplementation enhances the antioxidant statuses of the liver and plasma against oxidative stress in rats

Abstract: N-Carbamylglutamate (NCG), an effective precursor of arginine (ARG), can enhance ARG synthesis, increase intestinal growth, and improve reproductive performance. However, the antioxidant effect of NCG remains largely unknown. This study aims to survey the effects of ARG and NCG supplementation on the antioxidant statuses of the liver and plasma in rats under oxidative stress. Rats were fed for 30 days with one of the three iso-nitrogenous diets: basal diet (BD), BD plus 1% ARG, and BD plus 0.1% NCG. On day 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
47
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 50 publications
(61 reference statements)
9
47
2
Order By: Relevance
“…Our results suggested that L-Arg or NCG supplementation alleviated the liver function impairment in IUGR lambs as indicated by the decreased serum activity of AST and ALT following Arg or NCG supplementation. The dietary supplementation of L-Arg or NCG has been shown to decrease the AST and ALT levels in rats under oxidative stress [51]. According to our findings, the proinflammatory cytokine concentrations in plasma (IL-1ÎČ, TNF-α, and IL-6) were markedly elevated in IUGR suckling lambs, and the plasma levels showed a consistent trend with their respective gene expression identified in this research.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results suggested that L-Arg or NCG supplementation alleviated the liver function impairment in IUGR lambs as indicated by the decreased serum activity of AST and ALT following Arg or NCG supplementation. The dietary supplementation of L-Arg or NCG has been shown to decrease the AST and ALT levels in rats under oxidative stress [51]. According to our findings, the proinflammatory cytokine concentrations in plasma (IL-1ÎČ, TNF-α, and IL-6) were markedly elevated in IUGR suckling lambs, and the plasma levels showed a consistent trend with their respective gene expression identified in this research.…”
Section: Discussionsupporting
confidence: 83%
“…The adverse effects of IUGR on the above indices of liver growth were mitigated by the L-Arg and NCG supplementation as indicated by improving the protein : DNA ratio. Previous studies highlighted the protective effect of L-Arg against hepatic cell apoptosis [50,51] probably through the upregulation of the Bcl-2 antiapoptotic gene [52]. The IUGR-induced increase in hepatocyte apoptosis was further confirmed by the upregulated Bax and Fas expression; enhanced caspase-3, 8, and 9 activities; and elevated mitochondrial cytochrome C level, as well as the downregulated Bcl-2 expression in the liver of IUGR suckling lambs of our study.…”
Section: Discussionsupporting
confidence: 80%
“…The linearly increased Pro concentration in plasma following the increased NCG addition could be attributed to the Pro synthesis from Arg in the small intestine (Bertolo et al, 2003). As a kind of functional AA, Arg has many functions, including improvement of the production of animals and modulation of the related metabolism (Wu et al, 2004;Cao et al, 2016;. Our study suggested that linearly increased NCG addition improved milk protein content, which is consistent with our previous work (Chacher et al, 2014).…”
supporting
confidence: 90%
“…In Chacher et al (2014), the cows at early-stage lactation produced 40 kg/d of milk, which may be associated with severe oxidative stress due to the high metabolism rate at this stage (Lohrke et al, 2004). In nonruminant animals, Arg is thought to be insufficient under oxidative stress, and it can alleviate oxidative stress responses by improving antioxidative status (Cao et al, 2016). It is possible that Arg is insufficient for the dairy cows under the experimental conditions of Chacher et al (2014).…”
mentioning
confidence: 99%
“…l -Arg concentration directly determines the activity of arginase, the production of NO, urea, citrulline and ornithine [12]. Moreover, l -Arg is also implicated in insulin resistance [13,14], heat stress [15], oxidative stress [16], and many other environmental stresses. These physiological functions of l -Arg may be attributed to its regulating effects on some aging or resistance associated genes.…”
Section: Introductionmentioning
confidence: 99%